Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fmicb.2020.572921
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Resilience: Definition, Link to Health and Strategies for Intervention

Abstract: The gut microbiota is a new frontier in health and disease. Not only many diseases are associated with perturbed microbiota, but an increasing number of studies point to a cause-effect relationship. Defining a healthy microbiota is not possible at the current state of our knowledge mostly because of high interindividual variability. A resilient microbiota could be used as surrogate for healthy microbiota. In addition, the gut microbiota is an "organ" with frontline exposure to environmental changes and insults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 111 publications
(141 reference statements)
2
59
0
4
Order By: Relevance
“…In addition, Zn deficient chicks had expanded Proteobacteria, Enterobacteriaceae , and Enterococcus . As Zn is an essential mineral for many bacteria, the lower diversity and expansion of specific taxonomic groups indicates that those bacteria that can successfully compete for limited Zn or survive under Zn-limiting conditions are supported, but a reduction in diversity and expansion of the identified taxonomic groups have been associated with poorer gut health [ 34 ]. In a recent study, a Zn amino acid complex added to a wheat–rye based diet (at 60 mg/kg Zn) of broiler chickens increased Zn digestibility and villus length:crypt depth ratio, reduced abundance of some genera within the Proteobacteria phylum and oxidative stress, and improved starter phase feed conversion ratio compared to an equivalent amount of dietary Zn from Zn sulphate [ 35 ].…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
“…In addition, Zn deficient chicks had expanded Proteobacteria, Enterobacteriaceae , and Enterococcus . As Zn is an essential mineral for many bacteria, the lower diversity and expansion of specific taxonomic groups indicates that those bacteria that can successfully compete for limited Zn or survive under Zn-limiting conditions are supported, but a reduction in diversity and expansion of the identified taxonomic groups have been associated with poorer gut health [ 34 ]. In a recent study, a Zn amino acid complex added to a wheat–rye based diet (at 60 mg/kg Zn) of broiler chickens increased Zn digestibility and villus length:crypt depth ratio, reduced abundance of some genera within the Proteobacteria phylum and oxidative stress, and improved starter phase feed conversion ratio compared to an equivalent amount of dietary Zn from Zn sulphate [ 35 ].…”
Section: Zinc Copper and Manganese Influences On Intestinal Healthmentioning
confidence: 99%
“…A resistant community can be defined as one that resists perturbation, while a resilient community is one that recovers after perturbation [ 6 ]. A resilient community will likely stabilize into a fully functional state after transitioning through phases of perturbation and recovery [ 7 , 8 ]. Unresolved disruptions in microbiota lead to loss of colonization resistance [ 9 ], deleterious health consequences such as Clostridioides difficile infection [ 10 ], and altered metabolic functions important for host food processing [ 11 ], drug metabolism [ 12 ], and endocrine homeostasis (e.g., appetite regulation) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…antibiotics/dietary shifts) and return to their original state. Being non-resilient, a microbiome is likely to shift its composition permanently and stay at an altered new state instead of restoring to its original state of equilibrium (Dogra et al, 2020;Folke et al, 2004). Collectively, we disassembled the FR into one-to-one comparisons of between-taxa functional activities, and found that a global shift in functional roles of microbes towards a more heterogeneous pattern was a factor driving the decrease of FR and alteration of states in inflamed area in IBD patients.…”
Section: Discussionmentioning
confidence: 98%